2021
DOI: 10.1002/ange.202107161
|View full text |Cite
|
Sign up to set email alerts
|

Using Stereochemistry to Control Mechanical Properties in Thiol–Yne Click‐Hydrogels

Abstract: The stereochemistry of polymers has a profound impact on their mechanical properties. While this has been observed in thermoplastics, studies on how stereochemistry affects the bulk properties of swollen networks, such as hydrogels, are limited. Typically, changing the stiffness of a hydrogel is achieved at the cost of changing another parameter, that in turn affects the physical properties of the material and ultimately influences the cellular response. Herein, we report that by manipulating the stereochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…[ 48 ] Afterwards, they paid more attention to the relationship between stereochemistry and material properties and took advantage of which to construct stereo‐controlled elastomers, polymer networks, and sustainable (bio)materials. [ 49–55 ] For example, they used a degradable succinate‐based monomer for the polymerization and prepared a new type of resorbable elastomer‐like material for bionic soft tissue regeneration (Figure 1B). [ 50 ] Through altering the stoichiometry of succinate incorporation, the degradation rate of the materials could be tuned precisely while retaining control over the mechanical properties by maintaining the E / Z ratios of the vinyl groups.…”
Section: Progresses In X‐yne Click Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 48 ] Afterwards, they paid more attention to the relationship between stereochemistry and material properties and took advantage of which to construct stereo‐controlled elastomers, polymer networks, and sustainable (bio)materials. [ 49–55 ] For example, they used a degradable succinate‐based monomer for the polymerization and prepared a new type of resorbable elastomer‐like material for bionic soft tissue regeneration (Figure 1B). [ 50 ] Through altering the stoichiometry of succinate incorporation, the degradation rate of the materials could be tuned precisely while retaining control over the mechanical properties by maintaining the E / Z ratios of the vinyl groups.…”
Section: Progresses In X‐yne Click Polymerizationmentioning
confidence: 99%
“…Dove and coworkers have done a wealth of excellent works based on the organobase‐mediated thiol‐yne click polymerizations of ester or amide‐activated terminal alkynes and dithiols (Scheme 1H). [ 47–56 ] In 2016, they found that by judicious choice of organobase catalyst and solvent polarity, the stereochemistry of the formed vinyl group could be precisely controlled so as to remarkably impact on polymer properties, such as crystallization behaviors and mechanical and thermal properties. Thanks to the abundant alkyl chains in polymer skeletons and moderate crystallization, the resultant polymers could serve as thermally processable elastomer‐like materials with tunable mechanical properties.…”
Section: Progresses In X‐yne Click Polymerizationmentioning
confidence: 99%